(3TQM GdQSGdI GdfGUMI aj GdOdGFd GdQGSNIs - (3GdefUhQ HGddg GdbGFe HCeQ Gddgs
(3ChdgG (B:s
(3GdMeO ddg GdPi bgQS SdWGf Gdedhc SdWGfg hYdG Ydi TCf GdLHGHQI SCfg s
(3BNQgG (B:s
(3EfJgjfG Edi BNQ TQM GdQSGdI GdfGUMI hGdMeO ddg QH GdYGdejf hUdi Gddg hSde Ydi SjOfG eMeO hYdi Bdg GdWjHjf GdWGgQjf s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(226 D) s
Keywords: (3GdJhMjO hGdedd hGdfMds